A Palladium‐Catalyzed Carbonylation Approach to Eight‐Membered Lactam Derivatives with Antitumor Activity. Issue 9 (28th January 2016) - Mancuso, Raffaella; Raut, Dnyaneshwar S.; Marino, Nadia; De Luca, Giorgio; Giordano, Cinzia; Catalano, Stefania; Barone, Ines; Andò, Sebastiano; Gabriele, Bartolo
Abstract: The reactivity of 2‐(2‐alkynylphenoxy)anilines under PdI2 /KI‐catalyzed oxidative carbonylation conditions has been studied. Although a different reaction pathway could have been operating, N‐palladation followed by CO insertion was the favored pathway with all substrates tested, including those containing an internal or terminal triple bond. This led to the formation of a carbamoylpalladium species, the fate of which, as predicted by theoretical calculations, strongly depended on the nature of the substituent on the triple bond. In particular, 8‐ endo ‐dig cyclization preferentially occurred when the triple bond was terminal, leading to the formation of carbonylated ζ‐lactam derivatives, the structures of which have been confirmed by XRD analysis. These novel medium‐sized heterocyclic compounds showed antitumor activity against both estrogen receptor‐positive (MCF‐7) and triple negative (MDA‐MB‐231) breast cancer cell lines. In particular, ζ‐lactam3 j′ may represent a novel and promising antitumor agent because biological tests clearly demonstrate that this compound significantly reduces cell viability and motility in both MCF‐7 and MDA‐MB‐231 breast cancer cell lines, without affecting normal breast epithelial cell viability. Abstract : Making rings : A carbonylative ζ‐lactamization approach to eight‐membered heterocycles with an antiproliferative effect on MCF‐7 and MDA‐MB‐231 tumor cells is reported (see scheme). It is based on the multicomponent oxidative cyclocarbonylation–alkoxycarbonylation of readily available 2‐(2‐ethynylphenoxy)anilines, catalyzed by the PdI4 2− complex under relatively mild conditions.